Risk management practices: case evidence from Malaysian zakat Institutions / Nazifah Mustaffha - Mustaffha, Nazifah (2022)
Risk management is recognised as a crucial aspect of good governance. The implementation of risk management helps institutions to improve their management, use resources effectively and efficiently, and provide better services to their stakeholders. Due to the importance of risk management, such practice expands from the corporate to the public and government sectors with at least minimum adoption. As for zakat institutions, some of the institutions have practised risk management within their governance. This action is important to curb the issue of the reputation and performance of zakat institutions in the eyes of the public. However, notwithstanding the tremendous zakat institutions especially in Malaysia, risk management practice seems to be given less attention by the zakat managers. A review of major studies in the zakat management area proves that most of them focus on management in general with little consideration for the aspect of risk management. They do not provide direct evidence of risk management practice in zakat institutions. Thus, this study comes into existence to explore the types of risks and their relevant impacts on zakat institutions. Then, it explores the extent of current risk management practices in zakat institutions. Additionally, it is also conducted to examine the influencing factors for the adaptation of the risk management function in zakat institutions. Applying the case study methodology, this research conducts semi-structured interviews with the relevant risk management officers of seven voluntarily zakat institutions that participated in the study. Purposive sampling was used to select the institutions, which focused on those that have implemented formal risk management in their institutions. The findings demonstrated that risk management is a new practice in zakat institutions, with varying levels of maturity and advancement from one institution to the next. The success of risk management mainly relies on the internal management's willingness and readiness to have such a practice, supported by a few external motivational factors. The study finally proposes a risk management framework for zakat institutions in particular and other religious institutions in general. The proposed framework has undergone review with the risk management practitioners from one State Islamic Religious Council. This research has made a significant contribution to the assessment of zakat risk management, the identification of influencing factors that drive the implementation of risk management practice, and the proposition of a risk management framework to assist zakat institutions in developing or improving their risk management approaches that are aligned with the requirements of their institutional contexts.